Effect of oral zinc on hyperbilirubinemia in full term neonates - Patton Patton; Dedi Rachmadi; Abdurachman Sukadi (Indonesian Pediatric Society, 2011)
Background Oral zinc has been shown to reduce serum unconjugated bilirubin in animals, adolescents and low birth weight neonates. However, studies in healthy tenn neonates given oral zinc showed no reduction in hyperbilirubinemia based on time measurement in days. In order to improve accuracy, hyperbilirubinemia may be determined based on time measurements in hours.Objective To determine the effect of oral zinc on hyperbiliru-binemia in full term neonates, based on time measurement in hours, rather than days.Methods We conducted a randomized, double-blind clinical trial on healthy term neonates born spontaneously or through elective caesarean section in Hasan Sadikin Hospital from June to July 2010. Subjects were randomized into two groups: those receiving 5 mg of zinc sulphate and those receiving a placebo, sucrose, each twice daily. Serum total bilirubin level was examined at discharge and upon followô€‚up at day 5 of life. Factors which may be related to hyperbilirubinemia such as maternal age, infants' gender, umbilical cord bilirubin levels and type of feeding, were analyzed by Chi-square test. Hyperbilirubinemia persistence and comparison of survival distributions were analyzed by Kaplan-Meier survival analysis and Logrank test.Results Out of 60 subjects, 26 had hyperbilirubinemia. The mean duration of hyperbilirubinemia in the 15 subjects in the zinc group and 11 in the placebo group were 116.5 hours and 117.3 hours, respectively. There was no significant difference in hyperbilirubinemia duration between the two groups ( P=0.496, 95% CI 111.5 to 122.7). In addition, Chi-square analysis of factors which may be related to hyperbilirubinemia showed no significant difference between the two groups (P > 0.05).Conclusions Oral zinc 5 mg tMce daily made no significant difference in hyperbilirubinemia duration in full tenn neonates despite measuring in hours.